THE VISITOR SEGMENTATION OF JATILUWIH BALI - I Gusti Bagus Rai Utama; Ni Luh Christine Prawita Sari Suyasa (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2019)
Jatiluwih is listed as World Cultural Heritage by UNESCO on June 29, 2012. To increase the contribution of Jatiluwih as tourism attraction to local people, the research is needed to descript visitor profile, visitor purpose, and visitor's expectation after visiting Jatiluwih Tourism Attraction. These findings can be considered for local communities to conduct small businesses such as the recreational services, culinary, agribusiness, and business-related tourism services. This research is quantitative descriptive method which sample is chosen based on purposive sampling technique, foreign and also domestic tourists who visit at time total 107 respondents. The results show more female visitors than men, age groups between 21 to 30 years old, students or college students and dominant are educated undergraduate degree. Tourists who visit Jatiluwih dominant are domestic, followed by number of Australia, UK, and other countries. Tourists are motivated by the natural beauty of Jatiluwih, they are dominant repeaters, gather information from various sources of information, most of them spend time between one to two hours, they buy entry ticket directly at the counter, the amount of money spent between 50 thousand to 100 thousand rupiah, and the spending power of tourists between 500 thousand to one million rupiah per day.